Chemistry I - TERKHI, Mohammed Cherif (My University, 2024)
This handout, written for the first time in English at the University of Mostganem, is intended for first-year science and technology students of the L.M.D. (Bachelor-Master-Doctorate) program. It includes a reminder of the Chemistry Module I (Structure of Matter), illustrated by real photos and simplified diagrams. Students will follow the new undergraduate program easily by acquiring the fundamental concepts of matter structure. The course is made up of six chapters: The first chapter is devoted to reminders of fundamental concepts. The second chapter deals with the different components of matter, namely the proton, the neutron and the electron and the nuclear symbol. The third chapter introduces radioactivity. The fourth chapter describes two atomic models: the classical model and the quantum (or wave) model. The goal of the fifth chapter is to explain the principles of the periodic classification of chemical elements and their physicochemical properties. The last chapter is devoted to chemical bonding and the different types of bonds. This handout also includes sample exercises with answer keys to help the student better assimilate the module. keywords: structure of matter; atom; nuclei; electrons; radio activity; Bohr; periodic table
Course Material and Exercises with Answer Keys
Keywords: structure of matter; atom; nuclei; electrons; radio activity; Bohr; periodic table